The role of the local government unit in San Remigio, Antique in disaster relief operation the case of typhoon Frank - Claro, Darleen May P. (2009.)
Recently, a strong typhoon has visited the Philippines and it caused too much damaged and loss of properties among the affected people in the worst hit areas in the Philippines. The Philippines as an archipelagic country is very vulnerable to natural calamities such as typhoons, earthquakes, flooding and even the long drought. It simply says that a country, such as the Philippines should be more prepared and alert in responding to calamities and other disasters brought about by nature. There were already numbers of case studies about the disaster mitigation and preparedness of the Asian countries and one remarkable story of success is the case of Cuba. Cuba is also a third world country like the Philippines but what is more likeable about this is their disaster preparedness. The country also experienced tsunami and other natural hazards but they were able to counter the disaster without any records of casualties or injuries. This paper is entitled ?The Role of the Local Government Unit in San Remigio, Antique in Disaster Relief Operation: The Case of Typhoon Frank? which evaluates the efforts done by the local government in area of their responsibility in conducting relief operations to barangays that are affected by the calamity. This paper aims to propose recommendations to further improve disaster relief efforts not only in Antique but also in other regions of the Philippines
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2009.
Keywords: Disaster Relief Operation -- San Remigio Antique -- Tyhoon Frank